Fixed pigmented erythema due to cimetidine - Almamy Diabaté; Romain Boussou Aka; Bamba Vagamon; Hamdan Sarah Kourouma; Irenée Gué; Mamadou Kaloga (Our Dermatology Online, 2017)
Fixed pigmented erythema (EPF) is pathognomonic of drug-induced toxicity. Antisecretory drugs are among the most commonly not responsible drugs. EPF secondary to cimetidine administration has rarely been described. We report an EPF case during a cimetidine-based treatment in Bouake. A 43-year-old patient, HIV negative, consults for an EPF located on both sides of the breasts, on the 5th day of an antiulcer treatment comprising compressed cimetidine and gastric dressing based on phosphatase d 'aluminum. The diagnosis is made in front of the characteristic aspect of the lesion of EPF and the early reappearance of lesions recurring exactly in the same places, after the reintroduction of cimetidine. The discovery of an EPF imposes a strict etiological approach in search of the responsible drug. During anti-ulcer treatment, the practitioner should bear in mind the potential role of cimetidine.